Development of a guided imagery program for patients admitted to palliative care units - Coelho, Adriana (2019)
Background: Guided imagery (GI) is being increasingly used as a non-pharmacological intervention in different clinical settings. However, GI intervention programs have not yet been developed and adapted to patients admitted to palliative care units, which impedes their implementation. Thus, the need emerges to develop and validate a GI program. Objective: To develop and validate a GI program. Methodology: A descriptive study was conducted following the guidelines of the Medical Research Council for the development of complex interventions in 3 phases: identifying the evidence base, identifying/developing appropriate theory, modelling process and outcomes. Results: The development process resulted in a program consisting of 2 GI sessions to be implemented in the same week. Preliminary results on the implementation of a GI session suggest that the intervention is effective in increasing comfort. Conclusion: The characteristics of the GI program proved to be adjusted to the context and target population. The effectiveness of the GI program will be tested in a quasi-experimental study.